SAMI’NA WA ATHO’NA PHILOSOPHY IN THE PROCESS OF ACCOUNTING EDUCATION BASED ON ISLAMIC BOARDING SCHOOLS - Rofidatul Hasanah; Whedy Prasetyo; Ahmad Roziq (Universitas Airlangga, 2022)
This study aims to examine the philosophy of compliance with sami’na wa atho’na in the accountingeducation process. The object of this research is a Vocational High School as known as SMK MHI Jember, avocational school that is established and operates in Islamic boarding schools in Indonesia. This type ofresearch is a qualitative research with Husserl Phenomenology method. The resource persons in this studyamounted to 4 people, namely the chairman of the pesantren foundation, the treasurer of the foundation, thechairman of the MHI Vocational School, and the accounting teacher of the MHI Vocational School. This studyshows that the phenomenon of strict sami’na wa atho’na is not just student compliance with the teacher, but aspart of ethical development in the accounting education process at SMK MHI. Theoretically, the results of thisstudy can contribute to the accounting learning process which in the process emphasizes the usefulness of theaccounting discipline through the formation of the ethical character of students, as David Hume's theory ofUtilitarian Ethics, that an activity and policy is said to be good if it can provide benefits to the majority ofsociety. In addition, accounting educators and educational institutions that have study programs or accountingexpertise competencies can take the results of this study into consideration for manifesting the philosophy ofsami'na wa ato'na in the development of the accounting education curriculum in the era of the independentcurriculum and the 4.0 industrial revolution, where the moral crisis is be of serious concern.